Leaf Variegation and Impaired Chloroplast Development Caused by a Truncated CCT Domain Gene in albostrians Barley. Issue 7 (25th April 2019) - Li, Mingjiu; Hensel, Goetz; Mascher, Martin; Melzer, Michael; Budhagatapalli, Nagaveni; Rutten, Twan; Himmelbach, Axel; Beier, Sebastian; Korzun, Viktor; Kumlehn, Jochen; Börner, Thomas; Stein, Nils
Abstract : Leaf variegation in the barley mutant albostrians is caused by mutation of a single CCT–domain containing gene with residual activity, which is directed to the chloroplast. Abstract: Chloroplasts fuel plant development and growth by converting solar energy into chemical energy. They mature from proplastids through the concerted action of genes in both the organellar and the nuclear genome. Defects in such genes impair chloroplast development and may lead to pigment-deficient seedlings or seedlings with variegated leaves. Such mutants are instrumental as tools for dissecting genetic factors underlying the mechanisms involved in chloroplast biogenesis. Characterization of the green-white variegated albostrians mutant of barley ( Hordeum vulgare ) has greatly broadened the field of chloroplast biology, including the discovery of retrograde signaling. Here, we report identification of the ALBOSTRIANS gene HvAST (also known as Hordeum vulgare CCT Motif Family gene 7, HvCMF7 ) by positional cloning as well as its functional validation based on independently induced mutants by Targeting Induced Local Lesions in Genomes (TILLING) and RNA-guided clustered regularly interspaced short palindromic repeats-associated protein 9 endonuclease-mediated gene editing. The phenotypes of the independent HvAST mutants imply residual activity of HvCMF7 in the original albostrians allele conferring an imperfect penetrance of the variegated phenotype even at homozygous state of the mutation. HvCMF7 is a homolog of the Arabidopsis ( Arabidopsis thaliana ) CONSTANS, CO-like, and TOC1 ( CCT ) Motif transcription factor gene CHLOROPLAST IMPORT APPARATUS2, which was reported to be involved in the expression of nuclear genes essential for chloroplast biogenesis. Notably, in barley we localized HvCMF7 to the chloroplast, without any clear evidence for nuclear localization.